PEMBELAJARAN AKUATIK BAGI SISWA PRASEKOLAH - Ermawan Susanto (Jurnal Cakrawala Pendidikan, 2009)
AbstractAquatic Learning for Preschoolers. This article discusses an appropriate andfun method in aquatic learning for preschoolers and provides a guideline toimprove the process of aquatic learning for them. This article is based on literatureon aquatic learning for preschoolers. The process of preschool aquatic learningdeals with the development of childrens potentials through three aspects: basicpsychomotor skill, basic attitude, and basic understanding. The basic psychomotorskill consists of: (1) water entry, (2) buoyancy, (3) leg action, (4) balance in thewater, (5) arm action, and (6) breath control. The basic attitude consists of (1)bravery, (2) facility sharing, (3) respect for the rules, (4) attention to instructions,and (5) willingness to participate. The basic understanding consists of (1) classprocedures, (2) swimming pool rules, (3) playing rules, (4) instruction language,and (5) mechanics. The aquatic learning program should also consider cognitiveand affective aspects, besides the psychomotor aspect.Keywords: aquatic learning, preschool